Ultimate bearing capacity of jointed rocks as homogenous media - Fahimifar, A.; Sharifzadeh, Mostafa; Imani, M. (n/a, 2010)
In this paper, the bearing capacity of a jointed rock foundation was investigated using the code UDEC. The models include two joint sets with variable orientations and different joint spacing. Three values for orientation and joint spacing were selected and bearing capacity analysis was performed for each case. The results obtained from the numerical analyses were compared with the existing solutions in which both the rock matrix and joint properties are considered and then, the ranges in which the UDEC simulation takes the best agreement with the existing methods are specified. In other part of this paper, the effect of joint normal and shear stiffnesses on the bearing capacity was investigated. Results of this part show that the joint normal and shear stiffnesses don't have very significant effects on the bearing capacity of rock masses. The results obtained in this research show that by increasing the number of joints beneath the foundation, the bearing capacity will be reduced.